2006
DOI: 10.1017/s0967199406003625
|View full text |Cite
|
Sign up to set email alerts
|

Do age and extended culture affect the architecture of the zona pellucida of human oocytes and embryos?

Abstract: Advanced female age and extended in vitro culture have both been implicated in zona pellucida (ZP) hardening and thickening. This study aimed to determine the influence of (i) the woman's age and (ii) prolonged in vitro culture of embryos on ZP thickness and density using non-invasive polarized light (LC-PolScope) microscopy. ZP thickness and density (measured as retardance) were determined in oocytes, embryos and blastocysts in women undergoing intracytoplasmic sperm injection (ICSI) in two age groups (older,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 15 publications
2
26
2
Order By: Relevance
“…Moreover, when at least one embryo with a low IL-ZP area (that derives from an oocyte with a low IL-ZP area) is transferred, the pregnancy chance results to be approximately double than the one observed when embryos derived from oocytes with a high IL-ZP area are replaced (PR/ET 54.5 % vs. 21.4 %). These findings substantially agree with those of some previous studies suggesting an inverse relationship between IL-ZP thickness and oocyte competence [8][9][10][11][12][13], but were obtained used IL-ZP area measurement instead of IL-ZP thickness measurement. Indeed IL-ZP area appears to be more reliable and to have a lower intra-and interobserver variability than IL-ZP thickness, because it is automatically measured by the PLM software system that was used in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, when at least one embryo with a low IL-ZP area (that derives from an oocyte with a low IL-ZP area) is transferred, the pregnancy chance results to be approximately double than the one observed when embryos derived from oocytes with a high IL-ZP area are replaced (PR/ET 54.5 % vs. 21.4 %). These findings substantially agree with those of some previous studies suggesting an inverse relationship between IL-ZP thickness and oocyte competence [8][9][10][11][12][13], but were obtained used IL-ZP area measurement instead of IL-ZP thickness measurement. Indeed IL-ZP area appears to be more reliable and to have a lower intra-and interobserver variability than IL-ZP thickness, because it is automatically measured by the PLM software system that was used in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies on human oocytes reported that some birefringent characteristics of the meiotic spindle (MS) [5][6][7][8] and of the zona pellucida (ZP) [8][9][10][11][12][13] were associated with a high level of structural organization of the oocyte and could be positively related to the developmental potential of the embryo derived from it. These reports, however, were not fully convincing; especially those dealing with the MS were thoroughly criticized because the comparative analysis of the MS by confocal microscopy showed important discrepancies with PLM data [14].…”
Section: Introductionmentioning
confidence: 99%
“…The inner layer (IL) is the most birefringent and thicker and it is the main responsible for the changes in birefringence and thickness of the entire zona [23,25]. The birefringence of the zona pellucida has been reported to be positively correlated with zona thickness by some authors [13,23,25], but not by others [26]. The zona probably behaves as a whole functionally, though birefringence is seen only in its inner layer.…”
Section: Discussionmentioning
confidence: 99%
“…It is to be pointed out, however, that an apparent discrepancy about the average ZPT values exists among different works. This could be due to several factors including different scoring methods, high variability oocytes shape among patients and different culture conditions [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age, hormonal treatment, in vitro culture and cryopreservation have all been implicated in zona hardening or thickening, changes that make embryo hatching more difficult [37][38][39]. Yet, successful hatching of the embryo is essential if implantation is to occur.…”
Section: Assisted Reproductive Technologiesmentioning
confidence: 99%